ANALISIS PENGARUH ESG DISCLOSURE, FINANCIAL DISTRESS, DAN KOMPLEKSITAS AUDIT TERHADAP AUDIT REPORT LAG (Studi Empiris pada Perusahaan Energi dan Bahan Dasar yang Terdaftar di Bursa Efek Indonesia Periode 2021–2024) - Fakhrizal Ramadhana; Herry Laksito (Diponegoro Journal of Accounting, 2026)
This study examines the effects of Environmental, Social, and Governance (ESG) disclosure, financial distress, and audit complexity on audit report lag. Audit report lag is measured as the number of calendar days between the fiscal year-end and the date of the independent auditor’s report. ESG disclosure is proxied by the Bloomberg ESG Disclosure Score, financial distress by the Altman Z-Score, and audit complexity by the number of consolidated subsidiaries.The population comprises energy and basic materials companies listed on the Indonesia Stock Exchange during 2021–2024. Purposive sampling produced 39 companies and 156 firm-year observations; 150 observations were used in the regression model after data completeness screening. The study applies multiple linear regression using SPSS 25 and controls for firm size, Big Four auditor reputation, leverage, and return on equity.The results show that ESG disclosure has a negative and significant effect on audit report lag. The Altman Z-Score has a negative and significant coefficient, indicating substantively that stronger financial distress is associated with a longer audit completion period. Audit complexity has a positive and significant effect, suggesting that companies with more subsidiaries require more time to complete the audit. These findings extend audit report lag research by integrating non-financial transparency, financial risk, and corporate structural complexity in the Indonesian capital market.